2x+(-5)=3x+(-1)

Simple and best practice solution for 2x+(-5)=3x+(-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+(-5)=3x+(-1) equation:


Simplifying
2x + (-5) = 3x + (-1)
2x + -5 = 3x + (-1)

Reorder the terms:
-5 + 2x = 3x + (-1)
-5 + 2x = 3x + -1

Reorder the terms:
-5 + 2x = -1 + 3x

Solving
-5 + 2x = -1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + 2x + -3x = -1 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-5 + -1x = -1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + -1x = -1 + 0
-5 + -1x = -1

Add '5' to each side of the equation.
-5 + 5 + -1x = -1 + 5

Combine like terms: -5 + 5 = 0
0 + -1x = -1 + 5
-1x = -1 + 5

Combine like terms: -1 + 5 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| y-7=-5(x+8) | | secx-tanx=cscx-1/cotx | | 2m-0.5=1.7 | | 12y-30=18 | | -4(w+7)=24 | | 8=2x/0.200-x | | y+6=-7(x+5) | | (18-8x)/4x | | -11=x-5-1 | | 2y+4x-3w=19 | | -4x+68=0 | | 15-1(5m-4)=34 | | (x+3)(x+4)(2)=0 | | 3/4×2×12=j | | -38-12x=-8x+18 | | 5x^2-18x+8=0 | | .25=s-5 | | 5x^2-18x+9x=0 | | -7/5b=21 | | 7-7/5b=21 | | 7+x+1=360 | | X+x+1.25=4.75 | | 9/x-2/3=0 | | k+6+2=6 | | =32x+15000 | | h=-16t^2-24+100 | | 3x+4y=500 | | 0.5(x+2)=0.4(2x-2) | | 12-6r=3r+1 | | (1/4h | | 4n+4=36whatsn | | 24xy-8y+18x-6=0 |

Equations solver categories